2014
DOI: 10.3233/npm-14814008
|View full text |Cite
|
Sign up to set email alerts
|

Current trends and future challenges in neonatal parenteral nutrition

Abstract: A number of adaptations in total parenteral nutrition (TPN) protocols and practices for preterm neonates have been realized in the past several years, resulting in better survival and developmental outcomes. The early provision of appropriate concentrations of amino acids and energy are now recommended in evidence-based guidelines. Standardized TPN formulations are now available for many patients and may be associated with cost savings and improved adherence to guidelines. Several advantages of these preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
0
22
0
3
Order By: Relevance
“…In these cases, bilirubin levels in hemolysate must be measured. Parenteral alimentation with lipids is normally provided as nutrition to preterm infants or sickly newborns 19 . Although the bilirubin oxidase method is affected by the presence of serum hemoglobin and lipid emulsion 11 , we found in this study that hemolysate or serum containing emulsion did not affect unconjugated bilirubin measurement by the UnaG method.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, bilirubin levels in hemolysate must be measured. Parenteral alimentation with lipids is normally provided as nutrition to preterm infants or sickly newborns 19 . Although the bilirubin oxidase method is affected by the presence of serum hemoglobin and lipid emulsion 11 , we found in this study that hemolysate or serum containing emulsion did not affect unconjugated bilirubin measurement by the UnaG method.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that newborns fed exclusively with breast milk showed lower levels of phosphate than those receiving special formulas or mineral supplementation (16). In addition, preterm infants fed with unfortified human milk present rickets in 40% of the cases, compared to the 16% of those fed with special formulas (17). It has also been demonstrated that phosphate supplementation improves the biochemical markers of MBD in a cohort of preterm infants with low gestational age and birth weight more than in a cohort of preterm newborns with higher gestational age and birth weight (18).…”
Section: Introductionmentioning
confidence: 99%
“…Hypernatremia with weight gain suggests salt and water load and needs fluid and sodium restriction [ 148 ]. The daily protein and lipid requirement in ELBW/VLBW neonates is around 4-4.5 gm/kg/day and 3 gm/kg/day respectively [ 149 – 151 ]. The venous access should be secured in these newborn and intravenous fluids should be started at earliest to prevent hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%